PU.1 dictates β-amyloid-induced TREM2 expression upregulation in microglia in a transgenic model of Alzheimer’s disease - Wei, Zhen; Pan, Xiaodong; Cui, Xiaoli; Zhang, Jing; Dai, Xiaoman; Zeng, Yuqi; Chen, Xiaochun (Frontiers in Aging Neuroscience, 2025)
IntroductionMicroglial dysfunction is characteristic of Alzheimer’s disease (AD), with triggering receptor expressed on myeloid cells 2 (TREM2) and transcription factor PU.1 playing crucial roles. However, the relationship between TREM2 and PU.1 remains unclear.MethodsWe investigated TREM2 and PU.1 expression patterns in the 5×FAD mouse AD model. Experimental approaches included quantitative PCR, western blotting, immunofluorescence staining, chromatin immunoprecipitation, and luciferase reporter assays to examine the interaction between PU.1 and TREM2. The phagocytic function of microglial cells was evaluated using Aβ42 and Nile red fluorescent microsphere phagocytosis assays.ResultsTREM2 and PU.1 expression significantly correlated with brain β-amyloid (β) deposition. PU.1 directly interacted with the TREM2 promoter region, promoting its transcription and potently impacting microglial phagocytosis. PU.1 overexpression amplified TREM2 expression, while PU.1 knockdown reduced it.DiscussionOur findings reveal a novel regulatory mechanism where PU.1 directly modulates TREM2 transcription in activated microglia during AD progression. These insights highlight the potential of TREM2 and PU.1 as therapeutic targets in AD treatment.